Research on AC and DC leakage detection technology based on fluxgate principle. Issue 1 (18th August 2022) - Xu, Xiaowei; Tan, Xiangyu; Li, Wenyun; Ao, Gang; Li, Xueyuan; Xu, Xiaoqing; Zhang, Wenbin
Abstract: In view of the shortcomings of the traditional electromagnetic current transformer in the detection of pulsating DC and smooth DC, a leakage current detection method based on fluxgate magnetic field sensor is proposed in this paper. The leakage current is detected by the size of the magnetic field induced by the DRV425 fluxgate magnetic field sensor. At the same time, the magnetic core is designed to improve the sensitivity of the magnetic field sensor. Finally, the FFT is run in STM32 to identify the waveform of the leakage current from the frequency domain, and the tripping of the action mechanism is realized under different leakage current waveforms and different leakage current thresholds. The experimental results show that the method can effectively detect and identify the leakage current waveform, and can effectively improve the current status of the leakage protector.